Camera trap method effectively identifies small mammal species in forested habitats - Barbara Clucas; Sydney L. McCluskey (California Fish and Wildlife Journal)
Effective survey methods to detect small mammal species are often needed to develop conservation and management plans in forested ecosystems. The ability to use non-invasive methods to identify small mammal species in the field is particularly useful as live trapping can be time consuming and potentially harmful to the study species. We tested a camera trap method in a coastal redwood (Sequoia sempervirens) forest for small mammals, originally designed by Gracanin et al. (2019) and called the “selfie trap”, that uses a camera trap with a modified lens in a baited PVC tube. We determined if we could use this camera trap set-up on the ground to accurately identify small mammals to species to assess species diversity in a forested ecosystem as well as if it could withstand disturbance from larger mammals (e.g., bears). We surveyed for small mammals in areas of old-growth and second-growth coastal redwood forests in northwestern California. We detected 10 small mammal species and were able to identify most individuals to species including squirrel, chipmunk, mice, woodrat, shrew, vole and mole species. This camera trap set up also detected approximately 77% of small mammal species known to potentially occur in the area. Moreover, although larger mammals could interact with the camera trap set up, their disturbance was limited to when they were interacting with the trap, and the bait and camera set-up remained functional for subsequent small mammal detections. Thus, this method could be used instead of live trapping in complex forested ecosystems to effectively determine small mammal species presence, diversity, and activity levels, avoiding disturbance from large mammals.